Genetic Investigation of Complement Pathway Genes in Type 2 Diabetic Retinopathy: An Inflammatory Perspective - Ming Ming Yang; Jun Wang; Hong Ren; Yun Duan Sun; Jiao Jie Fan; Yan Teng; Yan Bo Li (Hindawi Limited, 2016)
Diabetic retinopathy (DR) has complex multifactorial pathogenesis. This study aimed to investigate the association of complement pathway genes with susceptibility to DR. Eight haplotype-tagging SNPs of SERPING1 and C5 were genotyped in 570 subjects with type 2 diabetes: 295 DR patients (138 nonproliferative DR [NPDR] and 157 proliferative DR [PDR]) and 275 diabetic controls. Among the six C5 SNPs, a marginal association was first detected between rs17611 and total DR patients (P=0.009, OR = 0.53 for recessive model). In stratification analysis, a significant decrease in the frequencies of G allele and GG homozygosity for rs17611 was observed in PDR patients compared with diabetic controls (Pcorr = 0.032, OR = 0.65 and Pcorr = 0.016, OR = 0.37, resp.); it was linked with a disease progression. A haplotype AA defined by the major alleles of rs17611 and rs1548782 was significantly predisposed to PDR with increased risk of 1.54 (Pcorr = 0.023). Regarding other variants in C5 and SERPING1, none of the tagging SNPs had a significant association with DR and its subgroups (all P>0.05). Our study revealed an association between DR and C5 polymorphisms with clinical significance, whereas SERPING1 is not a major genetic component of DR. Our data suggest a link of complement pathway with DR pathogenesis.